A bibliometric exploration of generative AI and critical thinking in educational research - MD IDRUS, NORAZAH; Abdul Ghani, Noor Amili; Ab Rahman, Hazlinah (Global Academic Excellence (M) Sdn Bhd, 2025)
Generative Artificial Intelligence (GenAI) has emerged as a transformative force in modern education. With the advent of large language models such as ChatGPT, new opportunities have arisen to enhance cognitive engagement and critical thinking among learners. However, despite rapid technological progress, a systematic understanding of how scholarly research conceptualizes and applies GenAI to foster critical thinking remains limited. This study conducts a bibliometric analysis to map global scholarship on Generative AI and critical thinking in educational research. Using Scopus as the primary database, 645 peer-reviewed documents published between 2020 and 2025 were analyzed using OpenRefine and VOSviewer. Findings reveal exponential growth in publications since 2023, driven by increased academic attention following the public release of ChatGPT. The United States and China lead in research output, while emerging contributors include the United Kingdom, Singapore, and Germany. Keyword network analysis reveals clusters centered around ‘language models’, ‘reasoning’, and ‘higher-order thinking’, indicating the integration of GenAI with cognitive skill development. This bibliometric exploration contributes to understanding the intellectual structure of this evolving field, emphasizing the dual role of GenAI as both a catalyst for educational innovation and a challenge for ethical, reflective practice.